Anti-inflammatory Test of Centella Asiatica Extract on Rat Induced by Cadmium - Hernayanti Hernayanti; Sri Lestari; Saryono Saryono; Puji Lestari (Molekul, 2021)
Cadmium is  a toxic heavy metal. The present of cadmium caused inflammation in liver. This study aims to know the anti inflammatory of Centella asiatica extract on rat induced by cadmium. This research was an experimental study using post test only control group design. Twenty four rats divided into six groups  with four replications, i.e group of healthy control (C1), negative control induced by CdSO4 with dosage 56 mg/kg for 14 days and treatment (C3-C6) with dosage of 100, 200 ,300 and 400 mg/kg of C. asiatica. The blood Cd, GST, GSH, TNF- α and COx2 were measured after a 21 days administration of C. asiatica. The data were analyzed by ANOVA test followed by Duncan test with a significance level of 5%. The result showed that administrating C.asiatica can neutralized cadmium, improve inflammation in liver.The conclusion of our research that C.asiatica extract can decrease Cd level, TNF-α and COx2 levels and increase GST and GSH level in rat induced by cadmium. A 200 mg/kg was the effective dosage to reduce Cd, TNF-α and COx2 levels and increase GST and GSH levels. Key words : anti inflammatory, Cd, Centella asiatica, GST, COX2